Feature Extraction of Composite Damage on Acoustic Emission Signals - Han Wen Qin; Zhou Jin Yu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
The aim of this study was to develop efficient methods to discriminate different damage mechanisms of composite. For this purpose, integration of Empirical Mode Decomposition (EMD) method and Hilbert-Huang Transform (HHT) was applied to define more relevant time-frequency descriptors. A complete methodology for the post-processing of the acoustic emission (AE) waveforms recorded during the quasi-static tension test of carbon fiber twill weave composite material was established in this work. AE signal is decomposed into several IMF components by means of EMD algorithm. The EMD can detach and extract all damage modes which consist in an AE signal. The HHT provide instantaneous frequencies in time-scale of an AE signal, which can be used as a new time-frequency descriptors of composite damage modes.